Efektifitas Pemanfaatan Artificial Intelligence (AI) dalam Penyusunan Proyek Mahasis dalam Mata Kuliah Sistem Perekonomian Indonesia - Khoerudin, Cep Miftah (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of Artificial Intelligence (AI) utilization in preparing course projects on the Indonesian Economic System and its impact on improving students’ conceptual understanding. The background of this research lies in the growing adoption of AI technology in academic settings, which, while facilitating learning efficiency, raises concerns about its influence on students’ analytical and reflective thinking. The study employs a quantitative descriptive approach using a survey of 40 students. Data were collected through a Likert-scale questionnaire and analyzed using a simple linear regression model with the assistance of SPSS version 26. The results show a correlation coefficient (R = 0.671) and a coefficient of determination (R² = 0.450), indicating that AI utilization contributes 45% to the improvement of students’ conceptual understanding. The ANOVA test (F = 31.865; Sig. = 0.000) and t-test (t = 5.646; Sig. = 0.000) confirm that the regression model is statistically significant both simultaneously and partially. These findings affirm that AI effectively enhances students’ academic performance and analytical quality but cannot fully substitute for critical and reflective human cognition. Therefore, AI should be wisely integrated into economics education as a cognitive partner that strengthens digital literacy, analytical reasoning, and intellectual independence.